Open, Repressive, Or Black Education? - Townsend, Mark (PINS-Psychology in Society, 2025)
On Friday, 31st May 1986 the Umlazi Extramural Division of the University of Zululand was host to a conference of relevance to all of us connected to black universities in South Africa. Funded by Ford Foundation and organized by the Association of Sociologists of South Africa (A.S.S.A.), the aim of the conference was to discuss the state of the social sciences at black SA universities. At least one delegate from each of the black universities was invited to give a short description of the situation at his or her university. It came as a shock to realize that most of the black universities were closed due to boycotts at the time of the conference. While some of the papers were stimulating, enlivening and critical, others were tired, boring and confused. George Orwell may perhaps have squirmed in his grave at the poor language usage of some of the delegates but, given the style of today’s academic discussion, this is hardly surprising. While this essay is mainly about the conference, it may be of interest to relate the issues raised here to the debate about South African universities that has arisen in the columns of the Times Higher Education Supplement, where a fellow of Robinson College, Cambridge University, Christopher Forsyth, and the rector of the University of Zululand, Prof A.C. Nkabinde, have been discussing similar issues.